Operations decisions and the influence of host-country institutions: an exploratory study under the Paraguayan 'Maquila regime' - Ferraz, Renan Lucas (2019)
When managing international manufacturing operations, firms are expected to make choices and face trade-offs. They operate within host-country institutional frameworks and are exposed to multiple and asymmetric institutional pressures, which somehow influence their decisions in multiple ways. Therefore, institutional frameworks set “the rules of the game” (North, 1990) and signal which choices are acceptable (Peng, 2002). Based on that, the purpose of this study is to comprehend how companies’ operations decisions are influenced by host-country formal institutions in international manufacturing. This is an exploratory research about two extreme cases of Brazilian textile-apparel companies that expanded their operations to Paraguay under the “Maquila regime”. It is guided by the institution-based view of international business. The study finds that four aspects of the Paraguayan institutional environment (i.e. environment uncertainty, high intervention of the government in business, inadequate number – or even lack – of market intermediaries and complexity and inefficiency of institutional mechanisms) shaped some operations decisions taken in the host country over time. A list of propositions is thus offered and help to synthetize the findings. The research contributes to the literature on global operations management by adding an institutional perspective to it and expanding the field towards an open system and beyond the factories’ walls, as suggested by Spring et al. (2017). It also brings elements for managerial (e.g. importance of the institutional environment for decisions taken by managers) and public policy (e.g. industrial policies and firm competitiveness) implications.